1994
DOI: 10.1901/jaba.1994.27-555
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Choice and Task Preference on the Work Performance of Adults With Severe Disabilities

Abstract: We evaluated the effects of choice versus the assignment of tasks of varying preferences on the work engagement of adults with severe disabilities. The combined results of two experiments suggest that the relative preference for a task may be an important variable in the effectiveness of choice for some individuals.DESCRIPTORS: choice, preference, severe disabilities, work performanceOne benefit of choice making for adults with severe disabilities is increased work engagement (Parsons, Reid, Reynolds, & Bumgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 2 publications
5
61
0
4
Order By: Relevance
“…Preference was nearly equivalent in the choice and no-choice conditions because the partic-REINFORCEMENT CHOICE ipants generally selected the high-preference items during choice sessions. Bambara et al (1994) replicated these results and observed no differences in on-task behavior during choice and no-choice conditions for 3 of 4 participants. Kennedy and Haring (1993) also obtained inconsistent findings when leisure activities provided during no-choice sessions were identical (i.e., yoked) to those selected by participants during choice sessions.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…Preference was nearly equivalent in the choice and no-choice conditions because the partic-REINFORCEMENT CHOICE ipants generally selected the high-preference items during choice sessions. Bambara et al (1994) replicated these results and observed no differences in on-task behavior during choice and no-choice conditions for 3 of 4 participants. Kennedy and Haring (1993) also obtained inconsistent findings when leisure activities provided during no-choice sessions were identical (i.e., yoked) to those selected by participants during choice sessions.…”
supporting
confidence: 55%
“…In previous studies (e.g., Dyer, 1987;Mason et al, 1989), choice-making opportunities improved responding when individuals' preference for available tasks or reinforcers was not held constant across choice-and nochoice conditions (i.e., when the no-choice REINFORCEMENT CHOICE condition did not produce access to the same stimuli provided in the choice condition). In contrast, choice did not influence responding (e.g., Smith et al, 1995) or produced inconsistent outcomes (Bambara et al, 1994;Kennedy & Haring, 1993;Vaughn & Horner, 1997) in studies that contained a control for preference in the no-choice condition. Thus, access to preferred stimuli rather than to choice-making opportunities per se may be most critical when establishing high rates of task performance in some individuals with severe to profound retardation.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, LEAs are accountable for demonstrating their efforts to assist the youth in self-determined post-school goals, including those related to employment. Third, researchers report identification of preferred employment is associated with improved work outcomes (Mithaug & Hanawalt, 1978) and reduced problem behavior (Bambara, Ager, & Koger, 1994).…”
mentioning
confidence: 99%